Characterization and evaluation of phenolic profiles and color as potential discriminating features among Spanish extra virgin olive oils with protected designation of origin. (15th February 2018) - Becerra-Herrera, Mercedes; Vélez-Martín, Alberto; Ramos-Merchante, Adrián; Richter, Pablo; Beltrán, Rafael; Sayago, Ana
Highlights: Phenolic profile characterization of the new cultivar named "serrana de espadán". Phenolic profile estimation by analysing hydroxytyrosol and 3, 4-DHPEA-EDA. PCA and LDA of phenolic profile give fingerprint of EVOOs geographical origin. Six phenolic compounds allows for an excellent differentiation of PDO EVOOs. Abstract: Changes in phenolic profiles and color parameters can help to differentiate between extra virgin olive oils (EVOOs) with protected designation of origin (PDO). Phenolic profile characterization and CIELAB parameters determination of 9 PDO EVOOs from Spain were developed. Both properties of EVOOs are very relevant to their commercialization and increase the product value. The Serrana de Espadán olive cultivar was characterized for the first time and showed the highest pinoresinol concentrations and clarities in these olive oils, which are important values for the product image. To detect fraudulent instrumental work and implement quality control, principal component analysis (PCA) and linear discriminant analysis (LDA) were performed. EVOO geographical origin and cultivar distributions were achieved with cumulative variances of 93.4% and 92.4%, respectively. A categorization of PDO EVOOs was proposed using the following 7 phenolic compounds: phenolic alcohols (tyrosol and hydroxytyrosol), 3, 4-DHPEA-EDA, 3, 4-DHPEA-EA, p -HPEA-EDA, pinoresinol and total phenolic compounds.